Low Health Literacy Is Associated With Frailty and Reduced Likelihood of Liver Transplant Listing: A Prospective Cohort Study. Issue 11 (7th October 2020) - Bittermann, Therese; Dwinnells, Kristen; Chadha, Sakshum; Wolf, Michael S.; Olthoff, Kim M.; Serper, Marina
Abstract : The effect of low health literacy (HL) on outcomes in end‐stage liver disease (ESLD) is largely unknown. The association of low HL on clinical outcomes was investigated in a prospective cohort of outpatients with ESLD undergoing liver transplantation (LT) evaluation. From 2014 to 2017, 276 patients underwent LT evaluation with assessments of liver disease severity, medical and psychosocial comorbidities, physical frailty, and malnutrition. Literacy was measured with the Newest Vital Sign, a brief validated assessment. Multivariate models assessed relationships between HL and clinical outcomes adjusting for clinical and psychosocial variables. The median Model for End‐Stage Liver Disease–sodium score of the study sample was 15 (interquartile range, 11‐19), 71 (25.7%) of candidates were frail, 117 (42.4%) had malnutrition, 151 (54.7%) had hepatic encephalopathy, 104 (37.7%) had low HL, and 85 (39.2%) had marginal or poor social support. Adjusting for education level, socioeconomic factors, and severity of illness, low HL was independently associated with physical frailty (adjusted odds ratio [aOR], 3.59; 95% confidence interval [CI], 1.50‐8.59; P  = 0.004) and not being wait‐listed (aOR 1.96; 95% CI, 1.03‐3.75; P  = 0.04). Strong social support attenuated the relationship between low HL and not being wait‐listed (aOR, 1.58; 95% CI, 0.74‐3.36; P  = 0.24). Low HL is common and a largely unrecognized risk factor for poor health outcomes among patients with ESLD. Patient‐oriented infrastructure and support are needed at the health system level to ensure all patients can successfully navigate the complex process of LT evaluation and wait‐listing.